PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA PERAWAT DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM UNIT KERJA DI KOTA YOGYAKARTA - Diana Sari Wijayanti, Irine; Wening Budiningrum, Endah; Hartadi, Agung (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study aims to analyze the influence of Occupational Health and Safety (K3) dimensions, namely work environment and human resources (HR) factors, on nurses' work productivity in the Inpatient Installation of a General Hospital in the Yogyakarta City Work Unit. The method used is quantitative with a multiple linear regression approach. The sample size of 96 nurses was selected through a purposive sampling technique. The results of the analysis show that simultaneously, both independent variables (work environment and HR) have a significant effect on nurses' work productivity (F count = 75.232 > F table = 2,3156, sig = 0.000). However, partially, both work environment factors (t count = 0.458) and HR (t count = 0.669) do not have a significant effect on productivity, because the t count values ??of both are smaller than the t table (1.989). The coefficient of determination (R²) value of 0.618 indicates that 61.8% of the variation in nurses' work productivity is explained by these two variables, while the rest is influenced by other factors. These findings demonstrate the importance of a holistic approach to improving nurse productivity, taking into account other OHS factors.